Poly[bis[μ2-3-(pyridin-4-yl)benzoato-κ3N:O,O′]lead(II)] - Guo, Yi-Ping; Wang, Hui; Li, Guo-Ting (Acta crystallographica. Section C, Crystal structure communications, 2013)
In the title compound, [Pb(C12H8NO2)2]n, the Pb atom sits on a crystallographic C2 axis and is six‐coordinate, ligated by two chelating carboxylate groups from two 3‐(pyridin‐4‐yl)benzoate (L) ligands and by two N atoms from another two ligands. Each ligand bridges two PbII centres, extending the structure into a corrugated two‐dimensional (4,4) net. The ligand L is conformationally chiral, with a torsion angle of 27.9 (12)° between the planes of its two rings. The torsion angle has the same sense throughout the structure, so that the extended two‐dimensional polymer is homochiral. Investigation of the thermal stability shows that the network is stable up to 613 K. In the absence of any stereoselective factor in the preparation of the compound, the enantiomeric purity of the crystal studied, based only on the torsional conformation of the ligand, implies that the bulk sample is a racemic conglomerate.